The Role of Islamic Counseling Based on the Concept of Tawakal in Addressing Baby Blues Symptoms - Putri, Mandarin; Dewi, Emi Puspita; Arsini, Yenti (Scidacplus, 2023)
This study aims to understand the role of Islamic counseling using the concept of tawakal in addressing baby blues symptoms. The research employs a qualitative method, with interviews and documentation as data collection techniques. The results show that client